The Effect of Combination of Cooperative Learning Type STAD With NHT on Problem Solving Ability in Class X Students at High School - Elga Farianti Djarawula; Nugroho Aji Prasetiyo; Zuni Mitasari (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims to determine the effect of the combination of the STAD learning model with NHT on the problem solving ability of students in class X Mipa 3 and 4 at SMA Negeri 9 Malang with the material being taught is kingdom Monera this research is a qusi-experimental research using a purposive sampling design. The population in this study amounted to 68 students who werea a combination of all class X in the school, while the sample was taken from two classes with 34 participants in the each class. The class was divided into control and experimental classes, where each class used conventional model for the control class and combination of STAD and NHT learning model for the experimental class. The study measures the problem solving ability of students. The data collection teachniques in the study were in the from of problem solving ability tests, observations, interview, documention with instruments in the from of lesson plans, LKPD, LKPD assement rubrics, observation sheets on the implementation of learning implematation plans, and problem solving ability instrument sheets in the from pre-test and post-test essays. Test analysis of research data used inferential statistical analysis with covariate analysis (anacova). The result of the hypothesis test showed that there was a significant effect, namely 0.008 < 0,05 from the learning model combination the STAD and NHT models with the kingdom monera material in class X at SMA Negeri 9 Malang.